2018
DOI: 10.1007/s00228-018-2451-3
|View full text |Cite
|
Sign up to set email alerts
|

Trends and variations in the prescribing of secondary preventative cardiovascular therapies for non-ST elevation myocardial infarction (NSTEMI) in Malaysia

Abstract: PurposeInformation is lacking on prescribing of preventative cardiovascular pharmacotherapies for patients with non-ST elevation myocardial infarction (NSTEMI) in the Asian region. This study examined the prescribing rate of these pharmacotherapies, comparing NSTEMI to STEMI, and variations across demographics and clinical factors within the NSTEMI group in the multi-ethnic Malaysian population.MethodsThis is a retrospective analysis of the Malaysian National Cardiovascular Disease Database-Acute Coronary Synd… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
10
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 10 publications
(15 citation statements)
references
References 38 publications
(61 reference statements)
3
10
0
Order By: Relevance
“…Optimal guideline‐indicated treatment of patients with NSTEMI is also affected by the availability of procedures, as well as governmental and hospital policies. Several studies have demonstrated wide geographical variation in the use of guideline‐indicated treatments for patients with NSTEMI, which is linked to hospital and geographical characteristics …”
Section: Challenges For the Treatment Of Patients With Nstemimentioning
confidence: 99%
See 4 more Smart Citations
“…Optimal guideline‐indicated treatment of patients with NSTEMI is also affected by the availability of procedures, as well as governmental and hospital policies. Several studies have demonstrated wide geographical variation in the use of guideline‐indicated treatments for patients with NSTEMI, which is linked to hospital and geographical characteristics …”
Section: Challenges For the Treatment Of Patients With Nstemimentioning
confidence: 99%
“…A study using the Malaysian National Cardiovascular Disease Database—ACS (NCVD‐ACS) registry showed geographical variations in prescribing rates for secondary preventive medications in patients with NSTEMI . For example, patients in East Malaysia were less likely to be prescribed P2Y 12 inhibitors or aspirin than patients in the Western region of the Malaysian Peninsular …”
Section: Challenges For the Treatment Of Patients With Nstemimentioning
confidence: 99%
See 3 more Smart Citations